Новые виды тромбикулид (Acariformes, Trombiculidae) с летучих мышей Азербайджана - Myлярская, Л.В. (Вестник зоологии, 1970)
Приводится описание обнаруженных на летучих мышах двух новых видов тромбикулид— Neotrombicula alizadei Muljarskaja sp. n. и Trombicula mussajesi Muljarskaja sp. n. A description is given of two new species of Trombiculidae found in bats: Neotrombicula alizadei Muljarskaj a sp. n. and Trombicula mussajevi Muljarskaj a sp. n. The first species is characterized by pentagona l scale and general formula EGBS — N—G3—2.1.1 — 1 —1.0.0. It differs from the typical representatives of the genus in absence of eyes, armed tarsus of palps (6Bs but not 7Bs) and other characters. It wa s found on Miniopterus schreibersi К u с h l., Myotis blythii Tome s and Rhinolophus megelyi M a ts с h i e. The second type is characterized by quadrangular scale and general formula E 5B— N—G3—3.1.2—1—0.0.0. It differs from the typical represenlative s of the genus in armed tarsus of palps, and peculiarities of scale structure and other characters. It was round on Rhinolophys mehelyi.